1997
DOI: 10.1006/viro.1997.8547
|View full text |Cite
|
Sign up to set email alerts
|

A Human IgG1 (b12) Specific for the CD4 Binding Site of HIV-1 Neutralizes by Inhibiting the Virus Fusion Entry Process, but b12 Fab Neutralizes by Inhibiting a Postfusion Event

Abstract: The human b12 IgG1, specific for the CD4 binding site of the gp120 of HIV-1, was prepared by recombinant DNA technology. It had a high neutralization rate constant (-3.5 x 10(5) M(-1) sec(-1)), although this is about 10-fold less than the values for the best poliovirus or influenza A virus MAbs. The recombinant b12 Fab neutralized well, with about one-tenth of the activity of b12 IgG. The mechanisms by which b12 IgG1 and its Fab neutralize HIV-1 IIIB on C8166 cells have been investigated. Neither inhibited att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 51 publications
3
52
1
Order By: Relevance
“…For the well-known MAb IgG1b12, directed against the CD4bs, conflicting results have been published. Ugolini et al reported inhibition of attachment (51), whereas McInerney et al showed inhibition of fusion by the whole antibody and an effect at an unidentified postfusion step for its Fab (26). In our hands, this antibody did not inhibit adsorption for either HIV-1 MN or PI.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…For the well-known MAb IgG1b12, directed against the CD4bs, conflicting results have been published. Ugolini et al reported inhibition of attachment (51), whereas McInerney et al showed inhibition of fusion by the whole antibody and an effect at an unidentified postfusion step for its Fab (26). In our hands, this antibody did not inhibit adsorption for either HIV-1 MN or PI.…”
Section: Discussionmentioning
confidence: 44%
“…The effect of such target cell interaction in the neutralization mechanism has been described for many viruses (13). For HIV-1, interaction with heparan sulfates has been reported to be involved in attachment (26). Although this nonspecific attachment has been well documented for some cell lines, such as MT-4 (37,40), no such heparan binding phenomena have been detected for PBMC and X4-or R5-type virus interactions (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2G12 recognizes a posttranslational glycan epitope on gp120 (2,3). CH103-CH106 (4), b12 (5,6), VRC01 (7), and numerous other mAbs with VRC01-like characteristics, such as VRC03, VRC-PG04, CH30-CH34, and the HAAD motif antibodies (7)(8)(9), recognize the CD4 binding site (CD4bs). HJ16 binds to an epitope near the CD4bs (10).…”
Section: Introductionmentioning
confidence: 99%
“…The four most broadly neutralizing MAbs were isolated from HIV-infected individuals, which has led to the hypothesis that it may be possible to elicit these antibodies of similar specificity and breadth by vaccination. MAbs b12, 2G12, 2F5, and 4E10 generally exhibit broad cross-clade neutralization of HIV-1 in vitro (3,5,22,27,38), although a small number of viruses have been identified that are not neutralized by any of the four MAbs at the concentrations tested (5). All four MAbs have been shown to protect against viral challenge in vivo in animal models when administered alone or in combination (1,15,17,25,26,35,43,50).…”
mentioning
confidence: 99%